THE PRINCIPLES OF PHONOLOGICAL WORD STRUCTURE COMPARISON OF RUSSIAN AND CHINESE LANGUAGES - A. N. Aleksakhin (Vestnik MGIMO-Universiteta)
The article is devoted to the phonological structure of words of Russian and Chinese languages. With phonological point of view the word as a Central significant unit of language is a sequence of consonants and vowel phonemes. A comparative study shows that the phonological structure of the Russian words prevail consonant phonemes and the phonological structure of the Chinese words prevail vowel phonemes. The phonological system of the Russian language is characterized by consonant dominant, and the phonological system of the Chinese language Mandarin is characterized by vocal dominant. In the vowel system of the Russian language there are six vowel phonemes, in the vowel system of the Chinese language Mandarin there are thirty-one vowel phonemes. The typical sound pattern of words of the Chinese language consists of vowel combinations. The strong (vowels differ in different effective modes of vocal cords) vowels are implemented in the even phonological position; the weak vowels are implemented in the left and right odd phonological positions of the syllabic matrix 0123. Consonant phonemes of the Chinese language are implemented only in the zero phonological position. The Sound variety of simple one-syllable words of the Chinese language is constructed by oppositions: twenty-five consonants in the zero position, thirty-one strong vowel phonemes in the even position, as well as three weak vowels in the left odd position and five weak vowels in the right odd position . The typical distribution of consonant and vowel phonemes is shown in the following examples of words: 0123 - guai «obedient», gudi «rotate», guài «strange». The opposition of weak vowels with a derivative phonological zero is also an effective method of making words: guai «obedient» - gai «must» - gua « blow» - ga «a dark corner». Both Russian and Chinese Synharmonia variety of sound words is supported by five derivative phonological zeros that are phonetically in Russian and Chinese are implemented by weak vowels. It is demonstrated for the first time that the Vowel harmony (Synharmonia) is a universal means for phonetic cel'nooformlennost' (phonetic unity) of words in Russian and Chinese languages.